Reforma al artículo 12 de la Ley de Régimen Tributario Interno y artículo 28 numeral 7 de su reglamento de aplicación, con respecto a la falta de especificación para la deducibilidad del gasto por amortización del activo intangible denominado goodwil - Rodríguez Ochoa, Katherine Johanna (2015)
This research has been developed due to the opportunity to reform the Law of Internal Tax Regime in Art was identified. 12 and Art. 28 of the Regulations Governing the Application of the Law on Internal Taxation, regarding the definition of amortization of intangible assets of the financial instrument called Goodwill as a deductible expense. In accordance with the Constitution of Ecuador's tax system should be governed under the principles of generality, progressivity, efficiency, administrative simplicity, retroactivity, equity, transparency and revenue adequacy; prioritizing direct and progressive taxation within which we have to tax corporate income. Art. 10 states that are deductible ITRL all costs and expenses incurred to obtain, maintain and improve the incomes of Ecuadorian source within the amortization of these expenses is. We basis of this, we say that the expenditure incurred during on which the taxpayer declares his taxable income is deducted from income to determine the taxable income tax, so its effect will be to reduce the taxable income; however, the law is very clear when it establishes the conditions and characteristics required such expenses to be considered deductible or not deductible. Goodwill In the case there is no express provision in this regard, that the rules for the amortization of investments deductible should be susceptible demerit which does not happen in the case of goodwill and that being an excess in the cost of acquisition fails with this provision but it is quite the opposite. That is why this work through the existing legal framework with respect to the tax treatment of that intangible asset is analyzed and compared with other legislation to substantiate the need for the proposal of a legal proposal to protect so held efficient rights of taxpayers and the proper administration of justice by the Tax Administration